Institutional governance and regulatory quality in building trust in pawnshop services - Muhammad Syahrudin; Wiwit Pawitri; Rheishi Alma Nazarani Sanusi (Journal of National Paradigm-Based Resilience Strategy, 2026)
Background: The rapid expansion of pawnshop services within emerging financial systems has increased their socio-economic importance and institutional relevance. However, existing financial trust literature remains predominantly bank-centric and continues to conceptualize trust primarily through customer satisfaction, service quality, and interpersonal interaction. Such approaches remain insufficient for explaining trust formation in collateral-based financial services characterized by custodial dependency, asymmetric vulnerability, and institutional exposure. This study aims to conceptualize institutional trust in pawnshop services as an outcome of governance–regulation alignment within alternative financial systems. Methods: This study adopts a conceptual theory-building design using an abductive reasoning approach. Drawing upon institutional theory, governance theory, and regulatory credibility theory, the study develops an integrative conceptual framework through iterative theoretical synthesis and analytical refinement. Findings: The study argues that institutional trust in pawnshop services does not emerge solely from individual perceptions of service quality, but from the institutional coherence between governance quality and regulatory credibility. The study introduces custodial vulnerability as a distinct conceptual construct describing the ethical, relational, and institutional exposure experienced by consumers in collateral-based financial transactions. The findings further indicate that transparent governance practices, procedural fairness, accountability mechanisms, and credible regulatory oversight collectively strengthen institutional legitimacy and public trust. Conclusion: This study reconceptualizes trust in pawnshop services as an emergent institutional outcome rather than merely an interpersonal or psychological perception. The proposed framework highlights the importance of governance–regulation alignment as a structural foundation of sustainable institutional trust within alternative financial services. Novelty/Originality of this Study: This study offers two primary conceptual contributions by introducing custodial vulnerability as a novel construct within collateral-based finance and by positioning governance–regulation alignment as the structural basis of institutional trust formation in pawnshop services.